Asim Al-Haidari His life and his political and cultural role - Hoshang Salih Najar; Barzan Muhammad ali (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
This study attempts to investigate one of the great Kurdish political and intellectual figures (Hasim Haydari) who had played a great role in the twentieth century in the development of the national freedom movement of Iraq. In addition, he has worked in many Kurdish and Arabic newspapers. He has also used literary genres to raise peoples’ awareness. In spite of all these great achievements, he has not been very well-appreciated and valued in the history of his nation. Therefore, we have dedicated this study to this under the title (Hasim Haydari 1921-1971 political and cultural role). Apart from the introduction, this study consists of two main parts. The first part is devoted to his biography and his role in the national freedom movement in Iraq and kurdistan. The second part Its focuses on the cultural role and an axis divided into two topics, the first talks about his writings and publication in newspapers and magazines, and the second deals with his articles translated in the political and literary aspects.